2020
DOI: 10.32479/ijefi.10147
|View full text |Cite
|
Sign up to set email alerts
|

Financial Stability and Bank Capital: The Case of Islamic Banks

Abstract: The purpose of this research is to empirically analyze Islamic Bank's financial stability, which consists in assessing the possible relationship between the risk of default (measured by z-score) and capital ratios while considering specific internal bank determinants. A regression analysis is derived on an unbalanced panel data including 405 observations of 81 Islamic banks established in 22 counties during the period of 2010-2014. To this purpose, our bank-specific data are collected from the websites of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
(69 reference statements)
1
8
0
Order By: Relevance
“…(2019) report but contrary to the findings of Agu and Nwankwo (2019), Sunday and Felicia (2020) and Daoud and Kammoun (2020). Furthermore, in the multiple regression results in…”
Section: Multicollinearity Testmentioning
confidence: 72%
See 1 more Smart Citation
“…(2019) report but contrary to the findings of Agu and Nwankwo (2019), Sunday and Felicia (2020) and Daoud and Kammoun (2020). Furthermore, in the multiple regression results in…”
Section: Multicollinearity Testmentioning
confidence: 72%
“…Results showed a negative but significant influence on the bank financial performance. Daoud and Kammoun (2020) Adegbie, Akintoye and Ashaolu (2019) examined the effect of corporate governance on the financial stability of deposit money banks in Nigeria. Ex-post facto research design was adopted for the study.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Studies found that Islamization followed by banks have the same insolvency risk as do conventional banks, however some of the studies suggest volt-faced scenario. Other studies (Daoud & Kammoun, 2020;Saeed, Izzeldin, Hassan, & Pappas, 2020;Smaoui, Mimouni, & Temimi, 2020) apprise that Islamic banks are higher on the scale of insolvency risk than do conventional banks.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A vast empirical literature compares Islamic banks (IBs) and conventional banks (CBs) in terms of their financial indicators (e.g. ; (Beck et al, 2013;Chowdhury et al, 2016;Daoud and Kammoun, 2017;Neifar and Gharbi, 2020;Daoud and Kammoun, 2020;Neifar, 2020;and Majeed and Zainab, 2021). The outcome results do not make clear cut about whether IBs are more Profitable, more liquid, more risky in credit or in insolvency, or more stable than CBs.…”
Section: Introductionmentioning
confidence: 99%